A study of ambient sensing as a strategy against monotony and boredom in space. Issue 3 (September 2022) - Tchakerian, Raffi; Morais, Renata; Patel, Sayjel V.; Cropper, Simon J.
Abstract: Psychological health is seriously impacted when humans are in isolated environments for long periods of time; monotony and boredom have been identified as serious stressors that can compromise the safety of space travel. This paper explores the potential of creativity and affective computation as future countermeasures to deep boredom in space, while also evaluating current countermeasures and highlighting their lack of flexibility. Responsiveness is required in order to address psychological health in space. The success of long-duration missions requires that major psycho-physiological challenges such as profound boredom be properly taken into account in the design of space habitats. By applying recent psychological research findings that assign a positive potential to boredom experiences, we reconsider the role of monotony and boredom in space travel. We propose the integration of artificial empathy systems within space habitats as a way to leverage this positive potential, by outlining tentative first steps towards 'Affective Computing Environments' (ACE) for space-flight. Through this process, space environments could potentially be imbued with the ability to perceive and respond to human emotional states. We conclude with a reflection on the importance of flexibility and responsiveness in strategies to mitigate monotony in deep space settings.